Obstructive sleep apnea in adults - Jorge Faber; Carolina Faber; Ana Paula Faber
ABSTRACT Introduction: Obstructive Sleep Apnea and Hypopnea Syndrome (OSAS) is a highly prevalent disease with serious consequences for the patients' lives. The treatment of the condition is mandatory for the improvement of the quality of life, as well as the life expectancy of the affected individuals. The most frequent treatments provided by dentistry are mandibular advancement devices (MAD) and orthognathic surgery with maxillomandibular advancement (MMA). This is possibly the only treatment option which offers high probability of cure. Objective: The present article provides a narrative review of OSAS from the perspective of 25 years of OSAS treatment clinical experience. Conclusion: MADs are a solid treatment option for primary snoring and mild or moderate OSAS. Patients with severe apnea who are non-adherent to CPAP may also be treated with MADs. Maxillomandibular advancement surgery is a safe and very effective treatment option to OSAS.